From Remembered School Objects to the Emotion of Objects - Sanchidrián Blanco, Carmen; Molina Poveda, María Dolores (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2023)
This study focuses on school objects from the perspective of the recollection of the students who used them. The data come from the responses to a survey about the favourite school object and the reasons for choosing it. The 285 objects mentioned by the 252 respondents were first grouped into 12 categories according to the object and then according to their social or cultural nature. The reasons given for the choice were classified into four categories to facilitate the analysis of the emotions elicited by these objects. The main results show that school objects are more than objects, they communicate ideas, imply values, and provoke emotions. Objects should be analysed in terms of their use and the reasons why they are remembered, which often involve personal relationships. New ways of approaching memories of these objects by educational historians are suggested.